The Effect of Reinforcement Ratio on the Wear Behaviour of AlB2 Flake Reinforced Metal Matrix Composites - Kayikci, R.; Savas, O.; Koksal, S.; Demir, A. (POLISH ACAD SCIENCES INST PHYSICS, 2014)
Aluminium boride composites (Al-AlB2) having two different volume fractions of reinforcing (AlB2), namely 4.0 and 10.0 per cent have been produced through synthesizing boron by reaction of boron oxide (B2O3) with liquid aluminium. Friction and wear characteristic of the composites have been investigated under dry sliding condition and results compared with pure aluminium. The wear rate increases with normal load and sliding speed and is significantly lower with the composites when compared to that of monolithic material. The coefficient of friction increased with increasing volume fraction of AlB2 reinforcement phase. The wear rate, however, decreased with increasing volume fraction of AlB2.
Keywords: Physics